2018
DOI: 10.1007/s12253-018-0428-2
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNAs in Colorectal Adenocarcinoma; an in silico Analysis

Abstract: Long noncoding RNAs (lncRNAs) are lengthy noncoding transcripts which are involved in critical signaling pathways including cell cycle and apoptosis so it is not surprising to see their altered expression in human tumors. Colorectal adenocarcinoma is one the most frequent malignancies worldwide. The role of lncRNAs in colorectal adenocarcinoma is not well understood. To study the significance of lncRNAs in colorectal adenocarcinoma, we retrieved 189 approved lncRNAs from HGNC. The genes were imported into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…However, other studies have shown that the expression of ZFAS1 was distinctly upregulated in ovarian cancer and related to survival, and could abolish its target gene SP1 by binding to miR-150 [27]. Current evident has indicated that ZFAS1 might act as a novel target and prognostic factor for the treatment of CRC [31], for instance, Ansari et al revealed that ZFAS1 allocated maximum alteration among the CRC samples and correlated with overall survival in patients [32]; Yan et al showed that ZFAS1 might serve as an oncogene by regulating its downstream target ZEB1 to promote epithelial-to-mesenchymal transition in CRC [33]. In our present study, we revealed that ZFAS1 was increased in CRC tissues compared with adjacent tissues, and had a close correlation with overall survival in CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have shown that the expression of ZFAS1 was distinctly upregulated in ovarian cancer and related to survival, and could abolish its target gene SP1 by binding to miR-150 [27]. Current evident has indicated that ZFAS1 might act as a novel target and prognostic factor for the treatment of CRC [31], for instance, Ansari et al revealed that ZFAS1 allocated maximum alteration among the CRC samples and correlated with overall survival in patients [32]; Yan et al showed that ZFAS1 might serve as an oncogene by regulating its downstream target ZEB1 to promote epithelial-to-mesenchymal transition in CRC [33]. In our present study, we revealed that ZFAS1 was increased in CRC tissues compared with adjacent tissues, and had a close correlation with overall survival in CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the expression of the same PVT1 isoform Sv-203, when determined together with the expression of Sv-206 and Sv-212 (two isoforms that are moderately expressed in colorectal tumors), was not associated with the clinicopathological features described above (69). Additional studies assessing PVT1 overall levels by means of high-throughput technologies such as microarrays or RNA sequencing, observed that high expression values were associated with shorter patient overall survival (67,152). Similarly, in gastric cancer, elevated PVT1 expression was found to be associated with high tumor stage (III-IV) (75)(76)(77)(78), lymph node metastasis (76) and overall/disease-free survival (78).…”
Section: Pvt1 As a Prognostic Biomarkermentioning
confidence: 99%
“…SNHG6 is localized preferentially in the cytoplasm by cytoplasmic and nuclear RNA fractions from some cancer cells, such as hepatocellular cells and colorectal cancer cells [9,10]. According to recent studies, SNHG6 is overexpressed in cancer tissues compared with the corresponding noncancerous tissues as well as in different cancer cell lines [11][12][13]. Upregulated SNHG6 relates to advanced tumor progression and short survival in patients [14,15].…”
Section: Snhg6-a Novel Player In Human Tumorsmentioning
confidence: 99%